KONSEP WAHYU DALAM AL-QUR’AN PERSPEKTIF SEKTE AHMADIYAH - Muhammad Saekul Mujahidin (Tanzil: Jurnal Studi Al-Quran, 2022)
The Prophet (saw.) said: “Difference among my Ummah is a mercy.” The emergence of new sects is a manifestation of the current current of human thought. This thought movement always affects the human condition, both positive and negative influences. The emergence of the Ahmadiyah sect, including the reformers of the Islamic world. Mirza Ghulam Ahmad is Al-Mahdi and Al-Masih. This study uses a library research approach. Revelation in the Ahmadiyah perspective has been confirmed in Q.S Al-Jumu‘ah [62]:3 and Q.S Aṣ-Ṣaff [61]:6, that both are the same and agree that the verse refers to the second coming of the Prophet Muhammad in the form of Mirza Ghulam Ahmad. Then the revelation referred to by other Ahmadiyah schools is not like the revelation in the Qur’an but the revelation of tajdid (renewal revelation) or muḥaddas revelation (revelation received directly through direct dialogue with God).